Trade and Women’s Economic Empowerment - Samy, Yiagadeesen. author. aut Link
XV, 162 p. 7 illus., 3 illus. in color.
Keywords: This open access book examines the relationship between trade and women’s economic empowerment by focusing on small and medium enterprises (SMEs) in six countries: Cambodia, Ghana, Madagascar, Nigeria, Senegal and Vietnam. The authors make use of both survey data and qualitative analysis to understand why and how trade can create more jobs for women, and how the jobs created are contributing to women’s empowerment. They propose strategies and policies for ensuring that women can benefit from trade. After providing the context for the research and reviewing the literature on trade and gender in the introductory chapter, the second chapter analyzes survey data collected for this project. This is followed by a qualitative analysis of the six country cases in the next two chapters: Cambodia and Vietnam (Chapter 3), followed by Ghana, Madagascar, Nigeria and Senegal (Chapter 4). The final chapter concludes with a summary of our findings and policy recommendations. AdedejiAdeniran is the Director of Research at the Center for the Study of the Economies of Africa, which is based in Abuja Nigeria. Madhurjya Kumar Dutta is currently the Director, Trade and Investment Facilitation Department of the Mekong Institute, Thailand. Jasmine Lal Fakmawii is Trade and Investment Program Coordinator at Mekong Institute, Thailand. Wen Hao currently works as the Program Coordinator in the Trade and Investment Facilitation Department at Mekong Institute, Thailand. Augustine Iraoya is Research Associate at Centre for the Study of the Economies of Africa, Nigeria. Yiagadeesen Samy is a Professor of International Affairs and currently the Director of the Norman Paterson School of International Affairs (NPSIA) at Carleton University.